Turkish-Greek relations : the security dilemma in the Aegean - Aydın, Mustafa; Ifantis, Kostas (ASAM series., 2004)
The discord between Turkey and Greece has grown deeper and wider over time, over a series of seemingly vital issues, which have at times brought the two countries to the brink of war. Yet in 1999 the two countries opened a dialogue on non-sensitive issues such as trade, the environment and tourism. The causes of the current rapprochement progress are explored in this book in relation both to the international environment which is increasingly conducive to this progress, and the significant domestic changes that both Greece and Turkey have experienced since the end of the Cold War. This.